2001
DOI: 10.1007/s002130000676
|View full text |Cite
|
Sign up to set email alerts
|

Influence of individual differences and chronic fluoxetine treatment on cocaine-seeking behavior in rats

Abstract: These results suggest that chronic fluoxetine treatment decreases motivation for cocaine when animals are in a cocaine-free state. Furthermore, individual differences in cocaine use are related to individual differences in sensitivity to the incentive motivational effects of cocaine priming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
61
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 46 publications
14
61
1
Order By: Relevance
“…Thus, cocaine-induced reinstatement is an acquired behavior specific to compulsive cocaine use and dissociable from cocaine-induced reward and psychomotor sensitization. This conclusion is consistent with previous research on individual rats with spontaneously high levels of cocaine consumption (Sutton et al, 2000;Baker et al, 2001). …”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, cocaine-induced reinstatement is an acquired behavior specific to compulsive cocaine use and dissociable from cocaine-induced reward and psychomotor sensitization. This conclusion is consistent with previous research on individual rats with spontaneously high levels of cocaine consumption (Sutton et al, 2000;Baker et al, 2001). …”
Section: Introductionsupporting
confidence: 93%
“…cocaine self-administration (Ahmed and Cador, 2006). A similar dissociation has also been previously reported in rats with the same daily duration of access to cocaine self-administration but with spontaneously low vs high levels of cocaine consumption (Sutton et al, 2000;Baker et al, 2001). In these studies, cocaine or amphetamine induced a robust reinstatement of cocaine-seeking behavior in rats with high cocaine intake but had no effect in rats with low cocaine intake.…”
Section: Discussionsupporting
confidence: 77%
“…The sensitization of prefrontal corticoaccumbens glutamate transmission is associated with increased sensitivity to cocaine reward and psychomotor activation (eg Pierce et al, 1996;McFarland et al, 2003). Thus, the present data are consistent with the reported effectiveness of selective serotonin reuptake inhibitors to attenuate cocaine self-administration and/or cocaine seeking in animal models of relapse (Baker et al, 2001;Tran-Nguyen et al, 2001;Czoty et al, 2002;Glatz et al, 2002) and pose a critical and selective role for MRN serotonin regulation of prefrontal cortex glutamate transmission in the enduring behavioral consequences of repeated cocaine administration.…”
Section: Serotonin Projections From the Mrn Regulate The Development supporting
confidence: 88%
“…Treatment with dexfenfluramine reduces responding for a CRf (Fletcher, 1995;Wilson et al, 2000), while whole-brain 5-HT neuron ablation enhances this behavior (Fletcher et al, 1999). In tests of drug-seeking behavior, dexfenfluramine and the SSRI fluoxetine also diminished the ability of a cocaine-paired stimulus to reinstate responding under extinction conditions (Baker et al, 2001;Burmeister et al, 2003). Furthermore, we have recently shown that another SSRI, citalopram, reduced responding for a CRf and a USRf (Browne et al, 2016).…”
Section: Introductionmentioning
confidence: 88%